Função pulmonar e depuração mucociliar nasal de cortadores de cana-de-açúcar brasileiros expostos à queima de biomassa - Ferreira, Aline Duarte; Ramos, Ercy Mara Cipulo; Trevisan, Iara B.; Leite, Marceli R.; Proença, Mahara; De Carvalho-junior, Luiz Carlos Soares; Toledo, Alessandra Choqueta; Ramos, Dionei (Fundação Jorge Duprat Figueiredo de Segurança e Medicina do Trabalho - FUNDACENTRO, 2018)
AbstractObjective:to evaluate the effects of sugarcane burning on lung function and mucociliary clearance in sugarcane workers.Methods:sixteen sugarcane workers were evaluated in two sequential periods: during the non-harvest season, in April/2011, and during the sugarcane burning harvest season, in October/2011. Mean values (standard deviation) of lung function and mucociliary clearance were evaluated through spirometry and the saccharin transit time (STT) test, respectively.Results:lung function decreased %FEF25-75 [99.31 (23.79) to 86.36 (27.41); p = 0.001]; %FEV1 [92.19 (13.24) to 90.44 (12.76); p = 0.022]; and FEV1/FVC [88.62 (5.68) to 84.90 (6.47); p = 0.004] during the harvest season compared with the non-harvest season. A significant decrease was found in saccharin transit time during the harvest [3 (1) min] season compared with the non-harvest season [8 (3) min] (p < 0.001).Conclusion:sugarcane workers present a decrease in %FEF25-75, %FEV1, FEV1/FVC ratio, and increase in nasal mucociliary transport velocity at the end of the harvest season.

ResumoObjetivos:avaliar a função pulmonar e a depuração mucociliar nasal de cortadores de cana-de-açúcar.Métodos:foram avaliados dezesseis cortadores de cana-de-açúcar em dois períodos: durante o plantio da cana-de-açúcar, em abril/2011, e no final da safra, no período de queima e colheita manual da cana-de-açúcar, outubro/2011. A função pulmonar e a depuração mucociliar foram avaliadas por meio da espirometria e do teste de tempo de trânsito da sacarina (TTS), respectivamente.Resultados:a função pulmonar apresentou diminuição no %FEF25-75 [99,31 (23,79) até 86,36 (27,41); p = 0,001]; %VEF1 [92,19 (13,24) até 90,44 (12,76); p = 0,022] e VEF1/CVF [88,62 (5.68) até 84,90 (6.47); p = 0,004] no período da colheita em comparação ao de plantio. Também houve uma diminuição significativa no resultado do teste do TTS na colheita [3 (1) min] em comparação ao plantio [8 (3) min] (p < 0,001).Conclusão:os cortadores de cana-de-açúcar apresentaram diminuição do %FEF25-75, %VEF1, do índice VEF1/CVF, e aumento da velocidade do transporte mucociliar nasal no final do período de colheita.
Lung function and nasal mucociliary clearance in Brazilian sugarcane cutters exposed to biomass burning
Keywords: rural worker; occupational health; mucociliary clearance; spirometry; trabalhador rural; saúde do trabalhador; depuração mucociliar; espirometria